Soucasný pohled na chirurgickou lécbu divertikulární choroby - Zonca, P; Jacobi, C A; Meyer, G P (Rozhledy v chirurgii, 2009)
AIM: The aim of our prospective dynamic cohort trial is the evaluation of indication for surgery for diverticular disease and the evaluation of morbidity and mortality. MATERIAL AND METHOD: All patients operated for diverticular disease and its complications were involved in the study. The conservatively treated patients were not involved. 104 patients with diverticular disease and its complication were operated from August 2007 till July 2008.46 men and 58 women at average age of 63.9 (31-85) years were in this group. 78 patients were electively operated in noninflammatory stage of diverticular disease. 3 patients of them had colovesical or enterocolical fistulas. An elective laparoscopic colon sigmoid resection was performed by 74 patients and a laparoscopic left hemicolectomy was performed by 4 patients. An end-to-end stapled colorectal suture was performed by all patients. An excision of fistula from urinary bladder and a segment resection of small bowel were performed in the case of fistula presence. In connection with previously repeated diverticulitis attacks or after previous surgeries, adhesiolysis was performed by 23 patients. 26 patients were operated for acute complication of diverticular disease. 24 patients of this group were operated for acute diverticulitis and 2 patients for diverticular bleeding. 23 colon sigmoideum resections, 2 left hemicolectomies, and once ileocecal resection were performed. The primary bowel suture was performed by 20 patients and Hartmaruts operation was performed by 4 patients. RESULTS: The indication for surgery follows the classification according to Hansen and Stock. The abdominal postoperative complications (wound infection, anastomotic leak, prolongated bowel atonia, and others) occurred by elective operated group in 9% and by acute operated group in 26.9%. The overall abdominal postoperative complications occurred in all the involved patients in 13.4%. The extraabdominal postoperative complications (urinary infection or retention, cardiopulmonary complications, trombosis/embolia, postoperative qualitative conscious disorder, renal insufficiency, and others) occurred by elective group in 19.6% and by acute operated group in 50%. Overall extraabdominal postoperative complications occurred in all involved patients in 26.90%. The mortality was 0%. The conversion rate in elective group was 3.8% (3 pts.). An anastomosis leak occurred once (1%) by elective operated patient. An acute reoperation with resection according to Hartmann was performed. A small bowel loop perforation by coincidental adhesiolysis occurred once. A small bowel defect was identified and sutured by early laparoscopic reoperation. The conversion rate in acute group was 23.1% (6 pts.). The colonoscopy was necessary on 3rd day by 1 patient after left hemicolectomy for splenic flexure bleeding. This examination revealed bleeding from diverticulum in hepatic flexure. An endoscopic treatment was performed. An abscess in small pelvis occurred by this patient (12th postoperative day) and open drainage was performed. There was no anastomosis leak in group with acutely operated patients. CONCLUSION: The usage of standard classification is suitable for operation's indication for diverticular disease and its complications. It helps to determine the type and operation's strategy. The acute complicated diveticulitis has high morbidity and mortality. The early indication of selected patients with diverticular disease for elective colon sigmoideum resection protects against possible complication in the case of next attack of diverticulitis. It concerns the patients with recidivated uncomplicated and complicated forms of disease as well. The primary conservative treatment with percutaneous CT navigated drainage allows a postponed elective surgery. The primary resection with suture is better than the two stage surgery. The primary laparoscopic resection is safe procedure in almost all the cases. The primary suture can be safely performed in all elective cases for uncomplicated diverticulitis, chronic fistulas, obstruction, for primarily conservatively treated stages Hinchey I and II and possibly for all the selected patients with Hinchey III and IV stages with MPI lower as 21.
Keywords: senioři; senioři nad 80 let; Diverticulitis; Middle Aged; mužské pohlaví; Adult; Elective Surgical Procedures; elektivní chirurgické výkony; Postoperative Complications; Aged, 80 and over; ženské pohlaví; Diverticulum, Colon; Humans; Acute Disease; lidé středního věku; divertikulitida; divertikl tlustého střeva; akutní nemoc; dospělí; Female; Aged; pooperační komplikace; lidé; Male